Oxygen deficient α-Fe2O3 photoelectrodes: a balance between enhanced electrical properties and trap-mediated losses1. Issue 7 (15th July 2015) - Forster, Mark; Potter, Richard J.; Ling, Yichuan; Yang, Yi; Klug, David R.; Li, Yat; Cowan, Alexander J.
<x xml:space="preserve">Abstract</x> Intrinsic doping of hematite through the inclusion of oxygen vacancies (VO) is being increasingly explored as a simple, low temperature route to preparing active water splitting α-Fe2O3−x photoelectrodes.